PL/SQL ROUTINE FOR UPDATING AND DISTRIBUTING SUBSISTENCE KITS TO REFUGEES FROM COUNTRIES AT WAR - Manzutti, Matheus de Lourenço; Ferreira, Hulgo Rafael; da Silva, Thiago Carvalho; Ribeiro, Patricia Bellin (Revista Interface Tecnológica, 2022)
The war started by the Russians in Ukraine forced thousands of Ukrainian citizens to flee to neighboring countries in search of protection, in which the UN and NATO helped these people through the distribution of subsistence kits. That said, the current work aims to demonstrate the creation of the database and its efficiency, with a PL/SQL routine to automate data through procedures and triggers, containing a function for a quick query in a Database Management System (DBMS) Oracle. Methodologically, an applied research is conceptualized, for the context of the war in Ukraine, in the reception of refugees with the help of partner countries, through scientific and journalistic articles, with thematic published from the year 2022, in the database of the Google Scholar, using the identifiers “war in Ukraine”, “UN”, “Ukrainian refugees” and electronic sites. Finally, the creation of the database and its proposed PL/SQL routines were fulfilled, and its automation with the data query was efficient.